Targeting MYCN in Molecularly Defined Malignant Brain Tumors - Borgenvik, Anna; Čančer, Matko; Hutter, Sonja; Swartling, Fredrik J. (Frontiers in Oncology, 2021)
Misregulation of MYC genes, causing MYC overexpression or protein stabilization, is observed in more than half of all cancers highlighting their important roles as oncogenes. Brain tumors in children have recently become the most lethal of all pediatric malignancies and the most common malignant primary adult brain tumor, glioblastoma, is still practically incurable. MYCN is one of three MYC family members and is crucial for normal brain development. It is associated with poor prognosis in many malignant pediatric brain tumor types and is focally amplified in specific adult brain tumors. Targeting MYCN has proved to be challenging due to its undruggable nature as a transcription factor and for its importance in regulating developmental programs also in healthy cells. In this review, we will discuss efforts made to circumvent the difficulty of targeting MYCN specifically by using direct or indirect measures to treat MYCN-driven brain tumors. We will further consider the mechanism of action of these efforts and hope to propose which molecularly defined brain tumor patients that would benefit from MYCN-directed precision therapies.